Supporting skill acquisition in cochlear implant surgery through virtual reality simulation. (4th March 2017) - Copson, Bridget; Wijewickrema, Sudanthi; Zhou, Yun; Piromchai, Patorn; Briggs, Robert; Bailey, James; Kennedy, Gregor; O'Leary, Stephen
Abstract : Objectives : To evaluate the effectiveness of a virtual reality (VR) temporal bone simulator in training cochlear implant surgery. Methods : We compared the performance of 12 otolaryngology registrars conducting simulated cochlear implant surgery before (pre-test) and after (post-tests) receiving training on a VR temporal bone surgery simulator with automated performance feedback. The post-test tasks were two temporal bones, one that was a mirror image of the temporal bone used as a pre-test and the other, a novel temporal bone. Participant performances were assessed by an otologist with a validated cochlear implant competency assessment tool. Structural damage was derived from an automatically generated simulator metric and compared between time points. Results : Wilcoxon signed-rank test showed that there was a significant improvement with a large effect size in the total performance scores between the pre-test (PT) and both the first and second post-tests (PT1, PT2) (PT-PT1: P  = 0.007, r  = 0.78, PT-PT2: P  = 0.005, r  = 0.82). Conclusion : The results of the study indicate that VR simulation with automated guidance can effectively be used to train surgeons in training complex temporal bone surgeries such as cochlear implantation.